THE EFFECT OF MACROMEDIA FLASH BASED LEARNING MEDIA TO IMPROVE THE ABILITY TO CALCULATE OF STUDENTS IN ELEMENTARY SCHOOL - Sidik, Ghany Taufik; Kelana, Jajang Bayu; Altaftazani, Deden Herdiana; Firdaus, Anugrah Ramadhan (PrimaryEdu : Journal of Primary Education, 2021)
This study aims to determine the effect of Macromedia Flash-based learning media to improve the numeracy ability of grade 1 students. The population in this study were 30 students of Class 1 at SDN Bina Harapan as an experimental group and 30 students at Class 1 at SDN 1 Sudimampir as a control group. This research is an experimental research using Quasi Experiment design. The technique in collecting data uses the method of observation, tests, and documentation. The analysis used is a non-parametric test using the man Whitney test. The results of the Mann Whitney analysis on the pretest data obtained the Asymp value. Sig. (2-tailed) = 0.532 > significance level a = 0.05 so that the initial abilities of students to count in the experimental class and the control class is the same while the results of the Mann Whitney analysis on posttest data obtained Asymp values. Sig. (2-tailed) = 0.005 < of the significance level a = 0.05 so that the final abilities of students are different. So, Macromedia Flash 8 based learning media significant influence on elementary students' numeracy skills